Implementing Cooperative Learning to Enhance Oral Proficiency Among EFL Learners - Nurmala Dewi; Elizia Maria Da Silva Caldei (Journal of English Language and Education, 2022)
The objective of this research is to investigate how the implementation of the cooperative learning method on students’ performance in the learning process and to find out its impact on students’ oral proficiency. In this study, the writer used a descriptive qualitative method. The data were collected by observation and doing pre-test and post-test. The research samples are thirty seventh-grade students in SMP Tarsisius 1 Jakarta. After applying the method, the result showed that cooperative learning could help students work together in groups and solve problems or tasks effectively. During the discussion, students are more engaged with others, and the interactions are more vivid. They have slight awareness to achieve the goals, especially in group work. In this condition, the cooperation among the intelligent and weak students has shown. So they do not only focus on the individual goal but the group goals. Besides, cooperative learning also supports enhancing students’ oral performance. The indication can be seen in pre-test and post-test scores. The students speaking scores were increased after the implementation of cooperative learning.